Faktor terkait Pekerjaan yang Berhubungan dengan Kejadian Migrain - Zahra, Tsurayya Fathma; Sutarto, Sutarto; Utama, Winda Trijayanthi (CV. Jasa Sukses Abadi, 2024)
Migraine is a neurovascular disease which is one of the main factors of disability in adults under 50 years. Migraines are generally characterized by headache attacks that are unilateral, recurrent, hereditary and multifactorial. The prevalence of migraine in the world reaches 10-14% with the highest incidence in North America, Central America and South America. In Indonesia alone, the prevalence of migraine has reached 3.5 million people with the highest coming from individuals aged 15-24 years. Until now, the exact cause of migraines is not known. However, there are many risk factors that can influence the occurrence of migraines, including work-related factors. Occupational factors related to migraines include work stress, environmental factors, and excessive use of electronic screens. Work-related stress can be caused by workload, time pressure, and relationships with coworkers. Work environmental factors can include excessive lighting, noise, changes in temperature and air pressure, and strong odors. Meanwhile, the use of electronic screens can influence migraines because they are related to the use of blue light, computer flashes, light reflections, and prolonged exposure to light. The diagnosis of migraine can be made through the results of the history and physical examination, and if necessary, supporting examinations can also be carried out to rule out other secondary causes that may influence migraine.